Macrophages and fibroblasts in cardiac fibrosis: interactions and transformation - Daehun Kim; Jea-Hyun Baek (Exploration of Immunology)
Cardiac fibrosis, characterized by excessive extracellular matrix (ECM) deposition, plays a central role in the progression of heart diseases such as myocardial infarction, heart failure, and hypertensive cardiomyopathy. The dynamic interplay between fibroblasts and macrophages is pivotal in regulating ECM remodeling and the fibrotic response. Fibroblasts, as primary ECM producers, undergo phenotypic changes during pathological conditions, transitioning into myofibroblasts that exacerbate fibrosis. Macrophages, both resident and non-resident, contribute to cardiac fibrosis by influencing fibroblast activation through cytokine secretion and direct cell interactions. Emerging evidence from preclinical studies highlights the transformation of macrophages into myofibroblast-like cells, known as macrophage-to-myofibroblast transformation (MMT), a key mechanism linking chronic inflammation to fibrosis. During MMT, macrophages acquire characteristics like myofibroblasts. This process is driven by signaling pathways such as TGF-β/Smad3, ALKBH5, and mineralocorticoid receptor (MR)/connective tissue growth factor (CTGF) pathways. Recent single-cell transcriptomics and lineage-tracing studies have provided deeper insights into the molecular regulation of MMT and its contribution to myocardial remodeling. Additionally, the balance between resident cardiac macrophages and monocyte-derived macrophages plays a crucial role in determining the fibrotic outcome following cardiac injury. This review discusses the cellular composition of the heart, the interactions between macrophages and fibroblasts, and the mechanisms driving MMT. By synthesizing these insights, we aim to evaluate MMT as a therapeutic target for mitigating cardiac fibrosis and improving clinical outcomes in cardiovascular diseases.